Design System Energy Sustainable Using Wind Turbine For Public Fish Cages Lightning at Belang Village in Southeast Minahasa - Verna Y.P. Bokau; Kristian Dame; Victory Polly; Steven Pandelaki (Fakultas Teknik Universitas Sam Ratulangi, 2019)
These paper present the designing system of wind turbine for public fish cages lighting at Belang Village in Southeast Minahasa. Belang is one of popular destination to find a fresh fish in north sulawesi, but the problem is the efficiency of electricity is not sufficient for the fish farmer. Propeller helps in the motor to generating electricity. Comprehensive research studies are carried out in order to measure the lighting resistances. The generated data from wind turbine can be seen using LCD 2x16 which connected with microcontroller Arduino Uno. Finally, conclusions are fully drawn.